Interaction With Educational Games in Hybrid Virtual Worlds. (June 2018) - Christopoulos, Athanasios; Conrad, Marc; Shukla, Mitul
This research links learner engagement with interactions when Hybrid Virtual Learning models are used. Various aspects have been considered, such as learners' prior experiences related to virtual worlds, their preconceptions regarding their use as a learning tool, and the impact that instructional designers' choices have on enhancing the opportunities for interactions. In this article, the impact that educational and leisure games have on university students' engagement is examined. The findings suggest that the use of game-like content can contribute positively to students' engagement, without, however, having a spectacular impact on the learning process.